Transient abnormal myelopoiesis without constitutional Down syndrome - Igne Kairiene; Vaidas Dirse; Ugnius Mickys; Audrone Muleviciene; Paresh Vyas; Jelena Rascon (Hygeia Press di Corridori Marinella, 2019)
Transient abnormal myelopoiesis (TAM) is a unique entity that usually occurs in children with Down syndrome (DS) or with trisomy 21 mosaicism. The somatic GATA1 mutation is a distinct feature of TAM. At presentation, TAM can resemble congenital leukemia (CL), which unlike TAM has an extremely poor prognosis and requires prompt therapeutic interventions. Therefore, correct and timely distinction between the two entities is crucial. We report a case of a phenotypically normal infant diagnosed with CL during the first weeks of life that retrospectively was reassessed as TAM. No acute myeloid leukemia (AML) specific mutations were found except for trisomy 21 confined exclusively to leukemic blasts. Retrospectively GATA1 mutation was also detected in malignant cells, but somatic genome appeared to be intact.